Plenary Sessions 2019
DOI: 10.1136/ijgc-2019-igcs.5
|View full text |Cite
|
Sign up to set email alerts
|

5 The good prognosis of immunoreactive subtype of high-grade serous ovarian cancer (HGSOC) is negatively impacted when obesity and lipid metabolism-related genes are highly expressed

Abstract: still treated according to a "one size fits all" approach. While tumor staging offers some stratification, the development of personalized treatment concepts remain elusive. Our group has recently validated the Proactive Molecular Risk Classifier for Endometrial Cancer (ProMisE), to distinguish clinically relevant prognostic groups. ENOC shares risk factors, genomics, and histology with it's endometrial counterpart. The aim of our study was to apply and investigate ProMisE in ovarian endometrioid carcinoma. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In addition, we have demonstrated that HGSOCs overexpressing obesity and lipid metabolism‐related genes share significant lower chances of achieving optimal debulking and having positive outcomes 57 . This group is enriched for the mesenchymal subtype 58 …”
Section: Management Of Gynecologic Cancers Among Obese and Morbidly O...mentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, we have demonstrated that HGSOCs overexpressing obesity and lipid metabolism‐related genes share significant lower chances of achieving optimal debulking and having positive outcomes 57 . This group is enriched for the mesenchymal subtype 58 …”
Section: Management Of Gynecologic Cancers Among Obese and Morbidly O...mentioning
confidence: 94%
“…57 This group is enriched for the mesenchymal subtype. 58 Radiotherapy either alone or in combination with chemotherapy constitutes the primary treatment for those gynecologic cancers not suitable for surgery or those locally advanced (i.e. uterine cervix cancer).…”
Section: Manag Ement Of Gynecolog Ic C An Cer S Among Ob E S E and Mo...mentioning
confidence: 99%